Design and Research of a Parallel Cable-Driven Force Feedback Master Hand - Duanjiao Li; Wenxing Sun; Junwen Yao; Yilong Chen; Yuhui Chen; Jieren Zheng; Yupeng Zou (IEEE Access)
Teleoperation systems enable operators to interact with remote environments or robots, allowing for remote control and task execution even when not physically present at the task location. Teleoperation robots with force feedback capabilities significantly enhance task success rates and reduce the risks associated with extreme operations. This paper proposes a parallel cable-driven force feedback master hand. Compared to traditional linkage-based force feedback master hands, cable-driven systems use lightweight elastic ropes or cables to transmit force and motion, offering greater flexibility and adaptability. This approach allows for simpler and more precise simulation of the forces encountered by the slave end in contact with the environment, providing operators with a more realistic experience. This study focuses on the development of a force feedback-enabled teleoperation master hand. Initially, a generative design of a six-cable parallel-driven force feedback master hand is presented. This master hand features a five-degree-of-freedom serial structure and integrates six motors to provide force feedback. The system’s functional modules are designed based on the overall control scheme. Subsequently, kinematic and dynamic analyses are conducted to derive the cable tension distribution scheme. A master-slave control system for the force feedback master hand is then established using Multibody dynamics, and force control simulations are performed based on planned trajectories to verify the accuracy of the kinematic analysis and the correctness of the tension distribution algorithm. Finally, displacement and force feedback experiments are conducted using the developed platform to validate the feasibility of the overall control scheme.